Attitudes and Factors Affecting Purchasing Decision Making Behavior of Fashionable Goods through Social Media by Female Consumers in the Bangkok Metropolitan Area - เชาว์ประสิทธิ์ ปิยภา; อาชารุ่งโรจน์ ไพบูลย์ (Siam Communication Review, 2018)
This research aimed to study the attitudes and factors affecting the purchasing decision making behavior of consumers through the use of social media of female consumers in the Bangkok Metropolitan area. The samples used in this study were female consumers who purchased fashionable goods via social media in the Bangkok Metropolitan area. Four hundred participants were assessed using quantitative research methods in the form of questionnaire. In-depth interviews with ten respondents were used as the qualitative research methodology. Based on the research, it was found that female consumers with different age, education level, occupation, average income per month and the type of social media used in the overall fashion choices had different purchasing decision - making behavior of consumers through the social media. The overall service marketing mix attitude was related with the purchasing decision - making behavior of fashionable goods through social media in terms of the period of time to select and decision for purchasing the fashion goods from the social media. The overall service marketing mix attitude, motivation factor and the trust factor were related with the purchasing decision - making behavior of fashionable goods through social media in terms of the cost for purchasing the fashion goods from the social media per time. The results of data analysis from in-depth interviews revealed that female consumers who purchased the fashionable goods from social media had marketing mix attitude regarding distribution channel and purchase process inconsistent with the quantitative research. They felt the process of buying fashion goods through social media was not all safe and were concerned about payment and shipping. In they preferred to buy fashion goods through the store rather than shopping through social media because they could see the actual product quality and it was easier to return the goods.